Cashew apple juice supplementation enhances leukocyte count by reducing oxidative stress after high-intensity exercise in trained and untrained men - Piyapong Prasertsri; Thapanee Roengrit; Yupaporn Kanpetta; Terdthai Tong-un; Supaporn Muchimapura; Jintanaporn Wattanathorn; Naruemon Leelayuwat (Taylor & Francis Group, 2019)
Background Cashew apple juice (CAJ) was shown to improve immunological mechanisms by regulating a balance between reactive oxygen species and antioxidant concentrations. However, no study exploring the effects of the CAJ and training status on the immune system and oxidative stress induced by exercise. Therefore, we investigated the effects of CAJ supplementation primarily on leukocyte counts and secondary on oxidative stress and cortisol changes after high-intensity exercise in trained and untrained men. Methods Ten moderately (endurance) trained (Age = 21.5 ± 0.97 yr., VO2max = 45.6 ± 4.12 mL/kgBM/min) and ten sedentary men (Age = 20.4 ± 2.72 yr., VO2peak = 32.2 ± 7.26 mL/kgBM/min) were randomized to ingest either daily CAJ or a placebo at 3.5 mL/kgBM/day for 4 weeks, with a four-week washout period. Before and after each period, they performed 20-min, high-intensity cycling (85% VO2max), with blood samples collected immediately preceding and the following exercise. Samples were analyzed to determine leukocyte counts, malondialdehyde, 8-isoprostane, and cortisol concentrations. A repeated measures analysis of variance was used to examine the effects of supplement and training status over time with an alpha level of 0.05. Results There was no interaction between supplement and training status on those variables before and after exercise. However, CAJ raised resting neutrophil counts and exercise-induced leukocyte counts in the trained group (all p < 0.05). Besides, CAJ significantly reduced plasma malondialdehyde concentrations at rest and after exercise and reduced the post-exercise plasma 8-isoprostane concentration in both groups of subjects (p < 0.05). Moreover, CAJ reduced plasma cortisol after exercise in the untrained subjects. Conclusions We suggest that 4-week CAJ supplementation can enhance exercise-induced leukocyte and resting neutrophil counts in trained men. The possible mechanism is a reduction in oxidative stress. However, the supplementation did not change the immune responses of untrained men, but it did reduce stress hormone concentrations. Trial registration number TCTR20181127002 Registered 26 November 2018 "retrospectively registered".